Keefektifan Implementasi CTL berbantuan Komik Matematika dan Langkah Penyelesaian Krulik dan Rudnick untuk Meningkatkan Kemampuan Pemahaman dan Disposisi Matematis Siswa - Widayanti, Christina; Dwidayati, Nurkaromah; Hendikawati, Putriaji (Unnes Journal of Mathematics Education, 2016)
This study aims to know the effectiveness of the CTL models aided by mathematical comics and Krulik and Rudnick’s steps in problem solving to improve the ability of student’s mathematical understanding and disposition. Population in this study were VIIIA grade students up to VIIIE of SMP Negeri 1 Pulokulon year 2015/2016 with a true experimental design types posttestonly control design and samples are chosen randomly. Data analysis that used in this study were an average of completeness test, the proportion test, the average difference test, and MannWhitney test. The results showed that (1) the ability of student’s mathematical understanding of the subject that have gained CTL models aided by mathematical comics and Krulik and Rudnick’s steps in problem solving have achieved the completeness in groups and classical; (2) the ability of student’s mathematical understanding of students who have gained CTL models aided by mathematical comics and Krulik and Rudnick’s steps in problem solving more than students with expository models aided by LKS, (3) the mathematical disposition of student’s who have gained CTL models aided by mathematical comics and Krulik and Rudnick’s steps in problem solving more than students with expository models aided by LKS.